Pembentukan Karakter Mahasiswa Yang Kreatif, Inovatif dan Kolaboratif Melalui Kegiatan PPAB UKMPR - Dewi, Ni Putu Sasmika; Pramana, Ida Bagus Kade Yoga; Purnamayasa, I Komang Widya (IAHN Gde Pudja Mataram, 2024)
The community service activity through the UKMPR New Member Training and Reception aims to introduce student organizations to new members while building organizational management skills, public speaking, and ethics. This activity involved 45 participants, four coaches, and lasted for six days, including preparation, implementation, and evaluation. The materials provided included an introduction to SMEs, leadership concepts, resource management, public communication, and organizational ethical values. The location of the activity at the Suranadi Temple Banquet Hall was chosen to create a new atmosphere that supported participant engagement. The results showed that participants were able to understand the vision, mission, and structure of the organization, develop public speaking skills, and apply organizational ethics. Factors driving success include the support of competent coaches and the enthusiasm of participants. However, there were obstacles such as limited facilities and infrastructure, low student participation, and the shy attitude of participants. Proposed solutions include improved facilities, innovative training methods, and a more interactive approach. This activity succeeded in improving participants' understanding of student organizations while equipping them with important relevant skills to support their future personal and professional development.